MASA KEMUNDURAN PENDIDIKAN ISLAM - Nilna Mayang Kencana Sirait; Dini Yuliani; Dwi Ananta Aura Ningrum; Dea Novita (Jurnal Al Wahyu, 2023)
In the Middle Ages, Islamic education began to decline gradually. On the other hand, Sufi education developed rapidly. This is in line with the situation where Muslims were destroyed by politics, Islam increasingly developed fatalism, thus making Muslims increasingly vulnerable to frustration and stagnation. and division. Intellectual education in the Middle Ages took over the development of the Western world until the Eastern world only accepted the Sufi way of thinking. In its golden age, Muslims were always united and complemented each other. After that, Islamic education no longer led to the development of Islamic civilization which Naturally, therefore this document talks about aspects of Islamic education and civilization which are increasingly deteriorating and weakening.